Ação antibacteriana de diferentes medicações intracanais frente a Enterococcus faecalis - Silva, Ana Rita Marques da (2015)
The present study aimed to introduce new intracanal medications and evaluate their antimicrobial effect against endodontic microorganisms involved in most of the cases of endodontic failure. The composition of the new formulations included 3% doxycycline hydrochloride (DX) or 3% nitrofurantoin (NIT), and a 2% chlorhexidine gel (CHX) was used as a positive control.This study was divided into three phases. The first phase evaluated the antimicrobial effect of the formulations DX and NIT against Gram-positive bacteria, Enterococcus faecalis and Staphylococcus aureus, Gram-negative bacteria, Escherichia coli and Pseudomonas aeruginosa, and fungus Candida albicans. The formulations were tested using the traditional agar diffusion test and the determination of the minimum inhibitory concentration (MIC) test. Based on the descriptive analysis of the agar diffusion test, DX presented a better antibacterial effect for most bacteria in the study. NIT values were lower than the CHX’s for all bacteria, with the exception of E. coli. DX and NIT were found ineffective for C. albicans. The descriptive analysis of MIC showed that DX was more effective than NIT, but when compared with CHX, it presented a lower antimicrobial effect. The second phase evaluated the antimicrobial effect against E. faecalis on the external root surface and the ability of diffusion through dentinal tubules of the new intracanal medications. Fifty human canine teeth were instrumented, sterilized and randomly divided into 5 groups of 10 teeth each, according to the formulation used as intracanal dressing: teeth sealed without medication (SM), negative control; CHX, positive control; placebo gel (PC); NIT and DX. After filling the root canals with the formulations, the teeth were incubated in the agar plates seeded with E. faecalis. The analysis of the halos revealed that DX had a larger inhibitory zone than CHX, while PC and NIT showed no antibacterial effect on the external root surface. The last phase evaluated the antimicrobial activity on infected root canals with E.faecalis. The chosen formulation was DX, as it obtained the best results on previous phases. Microbial samples were collected during three different time periods. The first sample (S1) was collected 21 days after contamination with E. faecalis; the second sample (S2) was collected 14 days under the effect of the intracanal medication, and the third sample (S3) 7 days after replacing the medication by BHI (Brain Heart Infusion) broth. The count of Colony Forming Units (CFU/mL) was statistically analyzed by repeated measures test (ANOVA) (p<0,05). All intracanal dressings significantly reduced the number of bacterial cells in the root canal after 14 days with medication (S2). After a period of 7 days with BHI broth (S3), the CFU counts of E. faecalis remained at low values in DX and CHX groups. The SM group, however, showed a significant increase of CFU in this period, to values similar to those of the initial contamination. These results show that DX was effective in eliminating E. faecalis from the root canal system, significantly decreasing the number of microorganisms after 14 days with medication and suggesting some substantivity after 7 days.Conclusion: From the two formulations suggested in this study, DX presented better antimicrobial effect against the microorganisms in the study (agar diffusion and MIC),supported by the effect on the external root surface and inside the root canal system. This new formulation containing DX can be considered as a possible intracanal dressing, namely in cases of endodontic failure.